Defining early carcinogenic markers for the prediction of the hazard potential of mineral fibres in an in vitro human 3D bronchial model - Vanessa Almonti; Serena Mirata; Mario Passalacqua; Stefania Vernazza; Sara Tirendi; Sara Ferrando; Beatrice Risso; Elena Grasselli; Giulia De Negri Atanasio; Anna Maria Bassi; Alessandro F. Gualtieri; Sonia Scarfì (Archives of Toxicology, 2026)
This study aimed to identify early carcinogenic markers to predict the hazard potential of mineral fibres using a human 3D bronchial model. Traditional 2D cell models inadequately mimic lung complexity, prompting the use of more physiologically relevant 3D systems. We investigated the effects of crocidolite (CRO) and two size fractions of chrysotile (≤ and > 5 μm length: CHR S and CHR L) to elucidate early toxicological mechanisms and relate them to the IARC key characteristics (KCs) of carcinogens. Initial analyses (MTT, TEER, and histology) at 24–48 h showed a transient acute toxicity and tissue resilience, indicating limited predictive value at this time point. However, after 12 d of exposure, fibre-treated tissues exhibited persistent alterations corresponding to established IARC KCs, suggesting the early onset of cell transformation pathways. Key findings included: sustained inflammatory signalling, characterized by prolonged overexpression of IL-1β, IL-6, and IL-8; ii) persistent genotoxicity, marked by the prolonged nuclear positivity of γH2AX, indicating DNA double-strand breaks without significant cell death; and iii) induction of fibrotic and epithelial-to-mesenchymal transition (EMT) signals, including the increased expression of key markers such as TGF-β, VEGF, ZEB-2, N-Cadherin, Vimentin, and Mesothelin. These alterations correspond to IARC KCs 2, 6, and 8. They were observed within a short time frame of tissue treatment and could serve as reliable, early predictive endpoints for in vitro toxicological tests. We propose that integrating these specific KC-based biosignatures in 3D lung models with physicochemical fibre characterization may provide a robust framework for predictive assessment of inhalable fibre carcinogenicity.

First fatal HPAIV H5N1 (Clade 2.3.4.4B) infection in a domestic cat in Italy - D. D'Annunzio; M. Moreno; T. Tosi; B. Bassi; M. Muscatello; B. Bortolami; D. Drago; F. Fusaro; M. Monne; P. Palumbo; S. Savegnago; T. Terregino; et al. (Journal of Comparative Pathology, 2025)

In vitro testing of hazardous mineral fibres: The issue of the concentration metric - Alessandro F. Gualtieri; Serena Mirata; Mario Passalacqua; Anna Maria Bassi; Sonia Scarfì (Environmental Toxicology and Pharmacology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Toxicity of size separated chrysotile fibres: The relevance of the macrophage-endothelial axis crosstalk - Serena Mirata; Vanessa Almonti; Mario Passalacqua; Stefania Vernazza; Anna Maria Bassi; Dario Di Giuseppe; Alessandro F. Gualtieri; Sonia Scarfì (Toxicology, 2025)

Non-cholera Vibrio spp. invasive infections in the summer following May 2023 flood disaster in Romagna, Italy: a case series - I. Zaghi; G. Tebano; E. Vanino; G. Vandi; M. Cricca; V. Sambri; M. Fantini; F. Di Antonio; M. Terzitta; E. Russo; F. Cristini; P. Bassi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Postmortem analysis of WWI human remains from Italian glaciers in rare environmental conditions - Daniel Gaudio; L. De Luca; V. Cirielli; M. Caccianiga; C. Bassi; N. Cappellozza; A. Galassi; F. Nicolis; C. Cattaneo (Archaeological and Anthropological Sciences, 2019)

Plant invasions on small Mediterranean islands: An overview - L. Celesti-Grapow; L. Bassi; G. Brundu; I. Camarda; E. Carli; G. D’Auria; E. Del Guacchio; G. Domina; G. Ferretti; B. Foggi; L. Lazzaro; P. Mazzola; et al. (Plant Biosystems, 2016)

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

Radiation hybrid QTL mapping of Tdes2 involved in the first meiotic division of wheat - F. M. Bassi; A. Kumar; Q. Zhang; E. Paux; E. Huttner; A. Kilian; R. Dizon; C. Feuillet; S. S. Xu; S. F. Kianian (Theoretical and Applied Genetics, 2013)

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Improvement of biomolecular methods for the identification and typing of Escherichia coli O157:H7 isolated from raw meat - A. Paris; S. Bonardi; C. Bacci; E. Boni; F. Salmi; L. Bassi; F. Brindani (Veterinary Research Communications, 2010)

Bitterness inheritance in apricot (P. armeniaca L.) seeds - P. Negri; D. Bassi; E. Magnanini; M. Rizzo; F. Bartolozzi (Tree Genetics & Genomes, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

A Zea mays 39-kDa thylakoid transglutaminase catalyses the modification by polyamines of light-harvesting complexII in a light-dependent way - M. Della Mea; A. Di Sandro; L. Dondini; S. Del Duca; F. Vantini; C. Bergamini; R. Bassi; D. Serafini-Fracassini (Planta, 2004)

Occurrence of the lutein-epoxide cycle in mistletoes of the Loranthaceae and Viscaceae - Shizue Matsubara; Tomas Morosinotto; Roberto Bassi; Anna-Luise Christian; Elke Fischer-Schliebs; Ulrich Lttge; Birgit Orthen; Augusto C. Franco; Fabio R. Scarano; Britta Frster; Barry J. Pogson; C. Barry Osmond (Planta, 2003)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Generalized cross-covariances and their estimation - H. R. Künsch; A. Papritz; F. Bassi (Mathematical Geosciences, 1997)